Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Simplify 7-5x-(3+5x)

Sagot :

Answer:

4-10x

Step-by-step explanation:

Hey there!

7 - 5x - (3 + 5x)

= 7 - 5x - 1(3 + 5x)

= 7 - 5x -1(3) - 1(5x)

= 7 - 5x - 3 - 5x

COMBINE the LIKE TERMS

= (-5x - 5x) + (7 - 3)

= -10x + 4

Therefore, your answer should be: -10x + 4

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)